Kecerdasan Emosional dan Hasil Belajar Matematika Siswa SMP - Rosida, Vivi (Indonesian Journal of Educational Studies, 2016)
Research of facto ex-post having the character of korelasional with aim to to know influence of emotional intellegence to result learn Student Class mathematics of VII SMP Country 1 Makassar. Intake of data conducted by using two instrument, that is emotional intellegence kuesioner and test result of learning which consist of double helix test and of essay. Result of analysis of statistic descriptive indicate that result learn Student Class mathematics categorized high. Emotional intellegence of student categorized high. Result of analysis of inferensial indicate that emotional intellegence have an effect on by significant to result learn sstudent slass mathematics of Â JHS. From result of analysis above, can be concluded that awareness of emotional intellegence have an effect on positive to result learn student slass mathematics.